The aesthetics of children’s drawings and the use of them in the production of designs for his room - Mohamed, Amani Shaaban Ali (Journal of Educational and Psychological Sciences, 2022)
This research aimed at identifying the characteristics of children’s drawings and how to benefit from children’s drawings to produce designs for children’s room furnishings. The problem of the study was to what extent children’s drawings are used in producing designs for his room? The aim of the research was to develop designs for children’s room furnishings inspired by their drawings, which are accepted by children. 10 designs for children’s room furnishings were drawn from children’s drawings, and the designs consisted of (tableau - hanging - sarsar mattress - bed sheet - curtain - carpet), and the study followed The descriptive approach and the quasi-experimental approach, and one of the results of the study was that it is possible to benefit from children’s drawings in making designs for children’s room furnishings, and children accept those designs